Beyond self-directed computer-assisted pronunciation learning: a qualitative investigation of a collaborative approach. Issue 7 (3rd September 2019) - Tsai, Pi-hua
Abstract: In foreign language education, instruction in pronunciation has received less attention than instruction in other language skills. Many teachers do not know how to teach correct pronunciation due to lack of knowledge in pronunciation pedagogy even if they want to or they assume that students pick it up on their own. With the development of technology, automatic speech recognition (ASR) software has been adopted in computer-assisted pronunciation training (CAPT) and has been found to be effective in facilitating pronunciation learning. Nevertheless, CAPT software still has its limitation. Very little research has been done on what difficulties students may encounter during practice with the system, such as how to read the feedback provided by the software. Moreover, very few CAPT studies investigated how collaborative learning can be integrated to augment the advantages of the technology. Efforts also have to be made on how to increase the enjoyment of learners using it when their motivation is curtailed by the unchanging feedback the CAPT system provides. The present study aims to investigate how those software users feel about the mediated assistance the system offers, their difficulty and attitudes toward using it, and, above all, how peers can help to mediate the pronunciation learning of students using MyET, a CAPT system designed in Taiwan. Two groups of junior college students ( N  = 60) practiced the system for 10 weeks with or without their peers. A qualitative investigation found that the collaborative group wrote down more statements about how they had benefited from the software than about their pronunciation difficulties. They also reported that the feedback helped raise their awareness of pronunciation errors. In the collaborative practice with the CAPT system, they revealed that they could explore more functions the software provided and had fun. This study further examines how peers interacted, analyzed, and discussed the effects of collaboration on computer-assisted pronunciation learning. Finally, suggestions were made for teachers interested in conducting CAPT in a collaborative context.